Stench : the making of the Thomas Court and the unmaking of America - Brock, David, 1962- (Alfred A. Knopf, 2024)
"A blistering expose of Clarence Thomas and the conservative regime of corruption that has usurped the Supreme Court - by a Democratic activist and former Republican political operative. Public confidence in the Supreme Court has plummeted to new lows in the last few years - and for good reason. In the past three decades, six conservative justices have gained a supermajority through questionable means: a dubious intervention in a presidential election, perjury during Senate testimony, and a GOP Senate Leader's unethical blockade of a Supreme Court nomination. Behind this strategic dismantling of our Supreme Court is a vast, well-funded political machine-backed by the extreme right-wing Federalist Society, the notoriously secretive Catholic organization Opus Dei, and GOP megadonors operating from behind closed doors. Armed with an insider's perspective from his time within the conservative movement, David Brock reveals how the efforts to stack the court in service of extreme right-wing interests stem from a decades-long strategy to weaponize our judicial system into an extension of the Republican party itself. Stench investigates the ethics scandals that surround Clarence Thomas and his wife, the rightwing activist Ginni Thomas, culling new material from Thomas' accusers, along with original reporting and Brock's first-hand knowledge of the inner workings of the GOP. Stench is a staggering expose, one that only Brock could write-exhaustive in its research and revelatory in its access to the world of what has effectively become the Thomas Court"--